Pulsed laser-deposited MoS2 thin films on W and Si: field emission and photoresponse studies - Late, Dattatray J.; Shaikh, Parvez A.; Khare, Ruchita T.; Kashid, Ranjit V.; Chaudhary, Minakshi V.; More, Mahendra A.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2014)
We report field electron emission investigations on pulsed laser-deposited molybdenum disulfide (MoS2) thin films on W-tip and Si substrates. In both cases, under the chosen growth conditions, the dry process of pulsed laser deposition (PLD) is seen to render a dense nanostructured morphology of MoS2, which is important for local electric field enhancement in field emission application. In the case of the MoS2 film on silicon (Si), the turn-on field required to draw an emission current density of 10 mu A/cm(2) is found to be 2.8 V/mu m. Interestingly, the MoS2 film on a tungsten (W) tip emitter delivers a large emission current density of similar to 30 mA/cm(2) at a relatively lower applied voltage of similar to 3.8 kV. Thus, the PLD-MoS2 can be utilized for various field emission-based applications. We also report our results of photodiode-like behavior in (n- and p- type) Si/PLDMoS2 heterostructures. Finally we show that MoS2 films deposited on flexible kapton substrate show a good photoresponse and recovery. Our investigations thus hold great promise for the development of PLD MoS2 films in application domains such as field emitters and heterostructures for novel nanoelectronic devices.
Keywords: field emission; MoS2; photodiode heterostructures; pulsed laser deposition; thin film